2022
DOI: 10.3390/v14071372
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy of HPV Positive and Negative Tonsillar Squamous Cell Carcinoma Cell Lines Reveals Synergy between CDK4/6, PI3K and Sometimes FGFR Inhibitors, but Rarely between PARP and WEE1 Inhibitors

Abstract: Human papillomavirus positive (HPV+) tonsillar and base of tongue squamous cell carcinoma (TSCC/BOTSCC) have a favorable outcome, but upon relapse, survival is poor and new therapeutical options are needed. Recently, we found synergistic effects by combining the food and drug administration approved (FDA) phosphoinositide 3-kinase (PI3K) and fibroblast-growth-factor-receptor (FGFR) inhibitors BYL719 and JNJ-42756493 on TSCC cell lines. Here this approach was extended and Cyclin-Dependent-Kinase-4/6 (CDK4/6) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Numerically, the cell numbers after dual inhibition in HSC4 and UT-SCC-60a reached only 74.3% and 64.5% of the numbers calculated for a strictly additive growth inhibition and we cannot rule out that some synergy may exist. But as these data do not provide a clear hint for a general and prominent effect in HNSCC cells, in line with a recent report [25] , this was not investigated in detail.
Fig.
…”
Section: Resultsmentioning
confidence: 41%
“…Numerically, the cell numbers after dual inhibition in HSC4 and UT-SCC-60a reached only 74.3% and 64.5% of the numbers calculated for a strictly additive growth inhibition and we cannot rule out that some synergy may exist. But as these data do not provide a clear hint for a general and prominent effect in HNSCC cells, in line with a recent report [25] , this was not investigated in detail.
Fig.
…”
Section: Resultsmentioning
confidence: 41%
“…This may be because SK-N-SH cell line was sensitive and lacked mutated p53 and it was difficult to observe further decreases in viability upon combination treatment, especially with doses that induced effects in more resistant cell lines. Our previous study showed that when combining PI3K and FGFR inhibitors in NB, MB and head and neck cancer cell lines, effects in cell lines that were particularly sensitive to one of the drugs were not observed ( 10 13 , 40 , 42 ). It is unknown why combining PD-0332991 + BYL719 resulted in enhanced inhibition in SK-N-AS, SK-N-BE(2)-C, SK-N-DZ and SK-N-FI, however all four cell lines have mutated p53.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we presented a Special Issue on “HPV in the head and neck region” which included several contributions to the overall knowledge of HPV in the head and neck region. In this second “Special Issue on HPV in the head and neck region 2.0”, eight original articles, one review, and one systematic review are presented [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
mentioning
confidence: 99%
“…An eighth original article described attempts to experimentally use various targeted therapies for HPV+ and HPV− tonsillar and base tongue cancer [ 8 ]. The authors used 4 cell lines of which three were HPV+ and one HPV-.…”
mentioning
confidence: 99%
See 1 more Smart Citation